Incidental Systemic Hypothermia as a Contributing Factor in Accidental Deaths: A Comparative Study in Jayawijaya, Indonesia - Auparay, Ferry; John Sigit Purnomo (Sriwijaya Journal of Forensic and Medicolegal, 2023)
Introduction: Accidental deaths pose a significant public health concern, especially in regions with challenging environmental conditions like Jayawijaya, Indonesia. This study investigates the role of incidental systemic hypothermia as a contributing factor in accidental deaths, comparing cases where hypothermia was identified to those where it was not. Methods: A retrospective comparative study was conducted, examining autopsy reports and medical records of accidental deaths in Jayawijaya from 2018 to 2023. Cases were classified into two groups: those with evidence of hypothermia and those without. Demographic data, circumstances of death, autopsy findings, and toxicology reports were analyzed. Results: A total of 350 accidental death cases were reviewed, with 78 (22.3%) exhibiting evidence of hypothermia. The hypothermia group had a significantly higher proportion of deaths occurring outdoors (p < 0.001) and during colder months (p = 0.025). Common causes of death in both groups included trauma, drowning, and poisoning. Hypothermia cases showed a trend towards lower core body temperatures at autopsy (p = 0.062). Conclusion: Incidental systemic hypothermia appears to be a contributing factor in a significant proportion of accidental deaths in Jayawijaya. Increased awareness of hypothermia risk, particularly in outdoor settings and during colder periods, is crucial for prevention and improved outcomes.